2010
DOI: 10.1074/jbc.m110.105775
|View full text |Cite
|
Sign up to set email alerts
|

N348I in HIV-1 Reverse Transcriptase Can Counteract the Nevirapine-mediated Bias toward RNase H Cleavage during Plus-strand Initiation

Abstract: Drug resistance-associated mutations in HIV-1 reverse transcriptase (RT) can affect the balance between polymerase and ribonuclease H (RNase H) activities of the enzyme. We have recently demonstrated that the N348I mutation in the connection domain causes selective dissociation from RNase H-competent complexes, whereas the functional integrity of the polymerase-competent complex remains largely unaffected. N348I has been associated with resistance to the non-nucleoside RT inhibitor (NNRTI), nevirapine; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
(26 reference statements)
2
24
0
Order By: Relevance
“…Our reported increase in the NVP IC 50 of p66 N348I /p51 N348I is consistent with values published elsewhere (2-3-fold increase) (31,57). These in vitro changes are smaller than those observed in cell-based assays for viruses harboring the same mutation (typically 7-8-fold and up to 27-fold) (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our reported increase in the NVP IC 50 of p66 N348I /p51 N348I is consistent with values published elsewhere (2-3-fold increase) (31,57). These in vitro changes are smaller than those observed in cell-based assays for viruses harboring the same mutation (typically 7-8-fold and up to 27-fold) (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 77%
“…Hence, NVP resistance of CSMs is expected to be affected by RNase H-independent mechanisms and possibly by RNase-dependent mechanisms. It is also possible that resistance is affected by sequence-specific effects on inhibitor susceptibility (57).…”
Section: Discussionmentioning
confidence: 99%
“…The connection mutations have been shown to impact DNA polymerization, enhance excision, reduce RNase H activity, and enhance NNRTI resistance 2022,24,80 . Interestingly, the connection mutations also enhanced the number of hubs and communities in the palm subdomain (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Transit-kinetic analysis has shown that E138K resistance to RPV is due mainly to an enhanced dissociation rate of RPV (11). N348I also confers resistance to NVP through decreased binding affinity (8) while inhibiting RNase H activity (10,77,99). Further biochemical and structural analyses may lead to the design of better NNRTIs with improved resistance profiles and potency.…”
Section: Discussionmentioning
confidence: 99%